1986
DOI: 10.1042/bj2380037
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines and HeLa-cell DNA replication

Abstract: HeLa cells were synchronized for S-phase DNA synthesis by the double thymidine-block procedure. A comparison was made of the polyamine content and S-phase DNA synthesis in cells from control cultures and cultures to which an inhibitor of polyamine biosynthesis, alpha-difluoromethylornithine, was added to the synchronization medium. Control cells showed a peak of synchronous DNA synthesis at 3 h and a maximum concentration of polyamines at 6-9 h after release of the second thymidine block. Cells from cultures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…The subject of polyamines and their role in cellular process has been the subject of considerable work over the years. Recently, polyamines have been implicated as regulators of cell growth acting at the level of DNA replication and as modulators of membrane fusion (7,14). While it was not a goal here to evaluate the role of putrescine in corn suspension cells, one might speculate that a correlation may exist between the high intracellular concentration of putrescine observed here and the rapidly dividing nature ofthe corn suspension culture.…”
Section: Discussionmentioning
confidence: 84%
“…The subject of polyamines and their role in cellular process has been the subject of considerable work over the years. Recently, polyamines have been implicated as regulators of cell growth acting at the level of DNA replication and as modulators of membrane fusion (7,14). While it was not a goal here to evaluate the role of putrescine in corn suspension cells, one might speculate that a correlation may exist between the high intracellular concentration of putrescine observed here and the rapidly dividing nature ofthe corn suspension culture.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, we began by synchronizing HeLa cells using the double-thymidine block procedure (31,32) to further isolate and characterize intracellular peptides from each individual phase of the cell cycle. As a result of the double-thymidine block, analyses by flow cytometry suggested that ϳ84% of HeLa cells were arrested in each phase of the cell cycle (G 1 , S, or G 2 /M) when compared with the asynchronous cell group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cell Cycle Synchronization by Double-thymidine BlockHeLa cells were synchronized using the double-thymidine block procedure (31,32). Thymidine (Sigma-Aldrich) was diluted in serum-free DMEM and stored at 4°C before use.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism by which polyamine depletion affects cell growth, however, is not clear. Several studies seem to indicate that polyamines are required for the transition from G1-(GO) to S-phase (11,16,26, 28,291, but there are other reports suggesting that the progression through S-phase is most severely affected by polyamine depletion (4,6,18,31). CHO cells which are adapted to grow without serum and are polyamine dependent, due to an arginase deficiency (8), accumulate in the S-and G2-phases when grown without polyamines (1).…”
Section: Discussionmentioning
confidence: 99%